2023
DOI: 10.7759/cureus.36731
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations in Aortic Arch Branching Pattern: A Computed Tomography Angiography Study

Abstract: Introduction: Variations in the branching pattern of the aortic arch (AA) are common. Modification of intravascular stents should be considered taking into account these AA branching variations. Identification of supra-aortic branching types and frequencies is important for specialists planning surgery in this region. In endovascular interventions to the AA, aortic stent grafts should be modified according to the variations of the branching patterns of the AA. In any surgical intervention to the region where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…There are many different mechanisms behind aortopathies, like the bicuspid aortic valve, inflammatory diseases, FMD, and heritable connective tissue disorders (e.g., Ehlers–Danlos syndrome) [ 56 , 57 ]. It has been reported that bovine arch variation is associated with the occurrence of aneurysms or type B aortic dissection [ 57 ], as well as with an early age at stroke presentation (on average, 53 years old), compared to normal branching pattern (61 years) [ 18 ]. Furthermore, type B dissections, such as the one in our present study, often occur in patients with normal-sized or only mildly enlarged aortae, and, therefore, are unpredictable [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many different mechanisms behind aortopathies, like the bicuspid aortic valve, inflammatory diseases, FMD, and heritable connective tissue disorders (e.g., Ehlers–Danlos syndrome) [ 56 , 57 ]. It has been reported that bovine arch variation is associated with the occurrence of aneurysms or type B aortic dissection [ 57 ], as well as with an early age at stroke presentation (on average, 53 years old), compared to normal branching pattern (61 years) [ 18 ]. Furthermore, type B dissections, such as the one in our present study, often occur in patients with normal-sized or only mildly enlarged aortae, and, therefore, are unpredictable [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, type B dissections, such as the one in our present study, often occur in patients with normal-sized or only mildly enlarged aortae, and, therefore, are unpredictable [ 46 ]. Malformative pathology of the aorta is often associated with congenital and/or valve diseases [ 56 , 57 ]. Aortic dissection and rupture are often consequences of disturbed shear stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation